Superendividamento: os perdedores do turbocapitalismo e a solução pelo capitalismo humanista - Caristina, Jean Eduardo Aguiar (2015)
The over-indebtedness is a phenomenon that is observed more and more constantly in turbo-capitalist consumer society, affecting family structures, excluding individuals of the economic process, producing losers. There are several his kind, and their causes. One is the rampant consumerism, the result of a ideological mistaken concept about development. This is because, under the neo-liberal nomenclature, many economies accepts more easily the markets domination, which place by logical and rationally planned means, own consumption policies that alienate consumers toward obtaining goods which gives them fancifully sense of belonging. The accelerated neo-liberal capitalism, mediatic and imperative is called turbo-capitalism. It is a kind of dynamic capitalism, seductive, and therefore of greater penetration in the local economy. The speed imposed by this new capitalism can not be avoided by governments, they are often victimized by their bureaucratic and limp structure and the strategic issues. Globalization, credit and deficiency of governments to provide welfare to individuals were instrumental in the turbo-capitalism became imperative in model market, which does not respect state borders or policies and impose their way of being as the only viable on the grounds that it is the path of development. The humanistic capitalism is the philosophy that directs the constitutional right of free enterprise to fulfill its primary mission: to serve men. It is through this humanism, consistent in applying the universal law of brotherhood, which the company may carry out the innate subjective rights of freedom, equality and property, making the economic order an instrument for development, in its different conceptions. Capitalism submits therefore that the constitutional order and she should respect. This work runs both ways. In the first, of capitalism, demonstrating its evolution, bewilderment and market influences in the new concept of development, human dignity and well-being. At the same time, it demonstrates how over-indebtedness has become inherent in this new social phenomenon conformation. In the end, it proposes solution to the problem of over-indebtedness, within the constitutional framework, and under the assumptions of humanistic philosophy of economic law, guided by the constitutional principle of brotherhood